Pandangan Hak Asasi Manusia Kebesasan Berpendapat di Media Sosial Hate Speech (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
One of the main pillars of effective democracy is freedom of speech, which allows everyone to express their opinions and perspectives freely without fear of facing repressive actions or unjustified barriers. Everyone is entitled to the freedom of association, assembly, and speech, as stated in Article 28E (3) of the 1945 Constitution. The aim of this research is to study the legal aspects of the existence of hate speech on social media. This study examines the current legal framework governing freedom of speech and efforts to protect human rights in relation to racial harassment by reviewing existing legal regulations. The research method employed is literature review (bibliographical study). In legal research, the normative jurisprudence method is based on legal provisions such as human rights books' regulations, as well as information from research journals related to the research subject. Initial research findings suggest that hate speech is not a form of freedom of speech, and society should not respond to hate speech with more hateful speech. Instead, they can report hate speech content to the Ministry of Communication and Informatics for removal. The Information and Electronic Transactions Law (ITE Law) can serve as a resolution due to the existence of hate speech on social media by proving the occurrence of hate speech, whether it involves defamation or hate speech against Ethnicity, Religion, Race, or Inter-group relations. Keywords: HAM, ITE Law, Hate Speech